Perancangan Sistem Perangkat Ajar Komputer Berbasis Multimedia Studi Kasus di SD Dian Kasih - Legowo, Nilo; Elidjen, Elidjen; Jefry, Hioe; Yangga, Ferry (Bina Nusantara University, 2011)
A teaching device is made to assist teaching and learning process in Dian Kasih Primary School with materials that match the school curriculum. Thus, children are able to understand the material presented better and be attracted more in using computer technology. The method used is an analysis which includes literature study, verbal interviews, questionnaires distribution and analysis. Meanwhile, the design method is done using the Waterfall model by following steps of multimedia software development. From the research results it can be concluded that the device helps with the learning system in Dian Kasih Primary School, helps students to understand the material presented by teachers more easily, provides interactive views, and be relatively easy to use.